Kingdom of Lesotho : Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waiver of Nonobservance of Performance Criterion, and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2012)
Lesotho's economic growth has weakened compared with the earlier forecast, owing to adverse exogenous shocks. In 2011/12, despite weather-related shocks (floods), robust growth was maintained. To address these shocks, the authorities have sought external assistance. Lesotho continued to face the challenges in rebuilding its international reserve cushion. The authorities continued commitment to implement reforms in improving the business climate to support private sector-led growth and economic diversification. The authorities have also requested a waiver for the missed cumulative quantitative performance.